Analisis Pengaruh Ukuran Batubara Terhadap Performa PLTU dengan Jenis Boiler Tipe Chain Grate - Muhammad Idris; Anggih Prasetyo Wibisono; Indra Hermawan; Iswandi Iswandi; Uun Novalia Harahap (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2022)
Based on ASME standard section VII, Part. 13, the recommended coal sizing for boiler stoker is 32 mm with a maximum mixture of 25% in 6 mm. PLTU Tanjung Balai Karimun (2x7 MW) which has a chain grate type of stoker boiler, for its operation using mostly in fine particle coal size with 58% in 31,5 mm – 2,38 mm and 17% in < 2,38 mm.  Regarding the use of non-standard ASME coal size on boiler stoker, the aim of this research is to know the effect of that coal to the performance of the power plant in the term of specific fuel consumption (SFC), turbine heat rate (THR), gross plant heat rate (GPHR), net plant heat rate (NPHR) and thermal efficiency of the cycle. After analyzing and calculating the operation data of the power plant, it is known that to produce 1 kWh of power, the power plant that uses fine particle coal size has a 26,80% higher on SFCgross and GPHR value, 25,87% higher on SFCnetto and NPHR value, and also 0,47% higher on THR value, but the thermal efficiency value is 4,43% smaller than when the power plant operates using standard ASME coal size. So it can be concluded that to produce 1 kWh the power plant when operating using non-standard ASME coal size requires more both energy and coal than when the power plant operates using standard ASME coal size